If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 3(1 + -2x) = -5(3x + -2) (1 * 3 + -2x * 3) = -5(3x + -2) (3 + -6x) = -5(3x + -2) Reorder the terms: 3 + -6x = -5(-2 + 3x) 3 + -6x = (-2 * -5 + 3x * -5) 3 + -6x = (10 + -15x) Solving 3 + -6x = 10 + -15x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '15x' to each side of the equation. 3 + -6x + 15x = 10 + -15x + 15x Combine like terms: -6x + 15x = 9x 3 + 9x = 10 + -15x + 15x Combine like terms: -15x + 15x = 0 3 + 9x = 10 + 0 3 + 9x = 10 Add '-3' to each side of the equation. 3 + -3 + 9x = 10 + -3 Combine like terms: 3 + -3 = 0 0 + 9x = 10 + -3 9x = 10 + -3 Combine like terms: 10 + -3 = 7 9x = 7 Divide each side by '9'. x = 0.7777777778 Simplifying x = 0.7777777778
| 8x-4=19-3x | | 2(w+5)+2w=70 | | V=imh | | -3(x-6)=-3-3x | | 2(4v-6)-2v=-8+5v | | 4y-3y-1=8 | | 2x-8=2(x-5) | | 2(3x+5)+2(8)=112 | | 0.25p=30 | | -5=-7(x+3)-3x | | 91-(6x+15)=6(x+4)+x | | 7x+17-5x+17=6 | | 21-8=x | | 5x-30=5x+30 | | 2m-m=13+16 | | 0.3(-0.9+8x)=3.2x | | 0.15-0.03(x+2)=-0.01(3-x) | | 1.33n+2n=-6.33+1.75n | | 8x+4x+7y=180 | | 2.4=14.4 | | 12x+(4x-1)=36 | | 1x+8=3 | | 7+9y=19-3y | | 12x-6x+204=12x+120 | | 2(d+7)= | | 6-2x(x+6)=3x+4 | | 6(2+5x)=12 | | 2a=a+11 | | -2-4x+8=-3(2-x)+4(8x+3) | | 8=8X+16+8X | | (x^4)+(x^2)-42=0 | | -91=9+8 |